Morphobiometric and molecular characterization of Bursaphelenchus Fuchs, 1937 (Nematoda: Aphelenchoididae) species associated with Pinus pinaster Ainton in Portugal - Naves, Ana Catarina Guerra Penas (2014)
Abstract - The genus Bursaphelenchus comprises almost 100 species mainly from the northern hemisphere, with conifers as the most important hosts. Among the various nematode species, the pine wood nematode (PWN), Bursaphelenchus xylophilus, is the casual agent of pine wilt disease (PWD), and the most important forest pest for pines worldwide, classified as an A1 quarantine organism within the European Union. In 1999 this nematode was detected for the first time in Portugal and Europa associated with maritime pine, Pinus pinaster. Following detection, a national program denominated "Programa Nacional de Luta contra o Nemátodo da Madeira do Pinheiro" (PROLUNP) was created to, among other objectives, determine the distribution of the PWN and its associated vector(s) and host(s), and therefore intensive surveys covering the entire country were conducted with thousands of wood samples and suspected insects being analyzed. This thesis presents the listing, distribution, frequency and the insects associated with Bursaphelenchus species found associated with maritime pine in Portugal, identifying and characterizing the various species by morphological, biometrical and molecular biology (ITS-RFLP and rDNA sequencing analysis) techniques. To achieve the objectives, a total of 4813 maritime pine wood samples and 3294 insects from 22 species and six families were individually analyzed. A total of nine Bursaphelenchus species were found, namely: B. antoniae, B. hellenicus, B. leoni, B. mucronatus, B. pinasteri, B. sexdentati, B. teratospicularis, B. tusciae and B. xylophilus, all of them (with the exception of B. xylophilus) being new records for Portugal. Some of the species appear to have a widespread distribution, such as B. leoni, B. teratospicularis and B. tusciae while others were very rarely found and apparently have a localized distribution range within the country, namely B. antoniae and B. mucronatus. The majority of the species is characteristic of the Mediterranean region and can also be found in countries such as Spain, Italy and Greece, reflecting the affinity of our fauna with those locations. The association of B. hellenicus and B. tusciae with maritime pine is here reported for the first time. Six of the Bursaphelenchus species were also found associated with insects, mainly from the family Scolytidae (Coleoptera). Some of these interactions were described for the first time, namely: B. hellenicus with both Ips sexdentatus and Hylurgus ligniperda, B. sexdentati with both H. ligniperda and Orthotomicus erosus and B. tusciae with H. ligniperda. The exclusive association of B. xylophilus with the cerambycid Monochamus galloprovincialis was also confirmed. The nematode's dauer juveniles were usually found in low numbers in the insect vectors (ca 10-100 per insect), although for B. xylophilus a few thousand specimens per insect were sometimes found. The location of the dauer juveniles differed according to the species, although they were more common under the elytra and wings of the adult insects. A species new to science was detected and formally described as B. antoniae, associated with Hylobius sp. (Coleoptera; Curculionidae) beetles. Morphologically, this new species is very similar to B. hylobianum, although it's distinct ITS-RFLP molecular pattern (with only the enzyme Haelll producing comparable restriction bands) and the failure of hybridization supported the two species as distinct entities. Additional phylogenetic analysis of the 18S rDNA sequence further supported the taxonomical proximity of B. antoniae with B. hylobianum. Concerning the PWN, detailed studies on the development and morphology of B. xylophilus were conducted, and comparative measurements of field-collected and laboratory-maintained populations demonstrated that nematodes from the second group displayed larger size in all morphometric parameters, which could derive from more adequate conditions of nourishment and/or temperature. Taxonomical studies on the development stages of B. xylophilus confirmed the existence of four propagative juvenile stages (J1,J2,J3 and J4), an adult stage with both sexes and two dispersal stages (jIII e jIV), with the measurements of the gonad length allowing the separation of the propagative stages. It is hoped that the acquired knowledge will be useful on future surveys of nematodes of the Bursaphelenchus genus collected from either wood material or insect vectors, and facilitate the correct distinction and identification of the various species which are now known to occur. ### Resumo - 0 género Bursaphelenchus compreende quase 100 espécies, distribuídas sobretudo nos países do hemisfério norte do globo terrestre. Embora algumas espécies já tenham sido detectadas em plantas herbáceas, os hospedeiros vegetais mais comuns deste género são as coníferas, particularmente pinheiros. 0 nemátode da madeira do pinheiro (NMP), Bursaphelenchus xylophilus, é considerado a espécie mais importante deste género uma vez que é o agente causal da doença da murchidão dos pinheiros ("pine wilt disease"). Originário dos Estados Unidos, onde não causa grande impacte, o NMP foi introduzido em alguns países da Ásia (China, Japão, Coreia e Taiwan) e mais recentemente na Europa (Portugal). Nestas regiões é responsável pela destruição de milhares de hectares de coníferas, assumindo uma elevada importância económica. Em Portugal, depois da sua detecção em 1999, associado a Pinus pinaster, foi implementado um programa nacional "Programa Nacional de Luta contra o Nemátodo da Madeira do Pinheiro" (PROLUNP) que permitiu determinar a área afectada pela praga (a sul do rio Tejo, península de Setúbal) bem como definir e implementar estratégias de controlo e prevenção da disseminação do NMP a outras zonas de Portugal. Recentemente, em Junho de 2008, foi confirmada a presença de B. xylophilus em outras regiões de Portugal levando as autoridades oficiais a definir todo o território continental como zona afectada e de restrição. As prospecções intensivas realizadas nos últimos anos incluíram a recolha e análise de milhares de amostras de madeira de pinheiro bem como de insectos associados ao pinheiro bravo conduzindo à identificação de várias espécies de Bursaphelenchus. Assim, os estudos conduzidos neste trabalho tiveram como objectivos efectuar uma caracterização morfológica, biométrica e molecular das espécies associadas a P. pinaster em Portugal bem como a sua distribuição geográfica e abundância. Os estudos biométricos foram realizados com populações extraídas directamente do meio natural. Foi ainda realizada uma pesquisa que permitiu identificar os insectos a que estão associadas essas espécies, os seus possíveis vectores. Foram analisadas no total 4813 amostras de P. pinaster e 3294 insectos (22 espécies pertencentes a seis famílias diferentes). Foram identificadas um total de nove espécies: B. antoniae n. sp., B. hellenicus, B. leoni, B. mucronatus, B. pinasteri, B. sexdentati, B. teratospicularis, B. tusciae e B. xylophilus. Foram realizados estudos morfológicos e biométricos de todas as espécies com excepção de B. mucronatus; o reduzido número de exemplares encontrados em apenas uma amostra foram utilizados para efectuar o diagnóstico molecular desta espécie (ITS-RFLP). Apesar de ter havido, sempre que possível, a confirmação molecular, na maioria dos casos a caracterização morfológica e biométrica permitiu a correcta identificação das espécies. Contudo, foi imprescindível a análise molecular em algumas amostras, nomeadamente para a identificação de B. xylophilus e B. sexdentati; dada a grande semelhança entre B. xylophilus e B. mucronatus e tendo sido encontradas algumas populações de B. xylophilus que possuíam fêmeas com cauda mucronada, foi necessária a realização da confirmação molecular. Com excepção de B. xylophilus, todas as outras espécies foram reportadas pela primeira vez em Portugal. Juntamente com B. xylophilus, B. pinasteri foi a espécie encontrada nas amostras de madeira de pinheiro com maior frequência. Algumas destas espécies como B. leoni, B. teratospicularis e B. tusciae foram reportadas em diferentes localidades do norte, centro e sul de Portugal, apresentando uma vasta distribuição geográfica; este resultado está em consonância com a forte associação destas espécies a climas mediterrânicos tal como acontece em Espanha, França, Itália e Grécia. Em oposição, espécies como B. antoniae e B. mucronatus foram encontradas apenas numa ocasião na região centro (Leiria) e norte (Figueira da Foz) do país, respectivamente. Bursaphelenchus mucronatus é igualmente pouco frequente em Espanha onde ocorre sobretudo na região norte, na Galiza. Esta espécie preferirá climas mais frios, ocorrendo com uma maior frequência nas regiões de latitude norte; esta análise é corroborada pela presença constante em países como Alemanha, Finlândia, França, Noruega, Rússia e Suécia. A nível mundial são descritas neste trabalho pela primeira vez as associações das espécies B. hellenicus e B. tusciae ao hospedeiro vegetal P. pinaster.